(untitled) (Web of Teachers: Inderscience Research, 2025)
This scientific article provides an in-depth analysis of the major socio-psychological characteristics influencing the enhancement of women’s activity. The research focuses on the mechanisms that stimulate women’s personal, family and professional engagement in the context of gender equality, social development, and economic growth. The impact of traditional stereotypes, self-esteem levels, motivation, and social support on the dynamics of women’s activity is examined based on theoretical and empirical evidence.